A fast trajectory planning framework with task-priority for space robot. (November 2018) - Luo, Jianjun; Yu, Min; Wang, Mingming; Yuan, Jianping
Abstract: This paper addresses trajectory planning issue for free-floating space robotic system which is designed to track a prescribed path simultaneously fulfilling imposed constraints such as collision avoidance and minimizing base attitude disturbance. Collision avoidance can be treated as inequality constraints as part of the trajectory planning. To generate smooth trajectory for robot motion, a novel local collision avoidance method considering multiple velocity damper constraints is proposed for non-strictly convex polyhedra. Moreover, we propose a task-priority handling strategy incorporated with a full-fledged Quadratic Programming(QP) procedure to solve the planning problem with sequential tasks. The proposed task-priority handling strategy enables a rapid adaptation of the space manipulators motion, which makes this strategy feasible for real-time planning. The trajectory planning framework with collision avoidance method and task-priority handling strategy were implemented and demonstrated via a kinematically redundant dual-arm space robotic system. Highlights: Trajectory planning framework with task-priority handling strategy for space robot. The task-priority handling strategy can handle both equality and inequality tasks. A novel local collision avoidance method for non-strictly convex polyhedral. Hildreth's QP Procedure is incorporated to efficiently solve the planning problem.